Determination of the Best Nonlinear Function in order to Estimate Brahman Female Cattle Growth - Husaini Karim Amrullah, A; Maharani, D; Tri Widayati, D (KnE Life Sciences, 2019)
Growth can be described by using a mathematical model. The appropriate mathematical model which is biologically and analytically easy to interpret is the nonlinear model. This research aimed to evaluate the nonlinear mathematical model in predicting Brahman female cattle growth. Data used in this research were the body weight recording of 738 Brahman female cattle, with age ranging from early birth (< 1 mo) to mature (60 mo), collected by Balai Pembibitan Ternak Unggul dan Hijauan Pakan Ternak (BPTU-HPT) [Breeding Center for Good Livestock and Animal Feed] Sembawa from 2012 to 2015. Data were analyzed using four nonlinear mathematical model: Brody, Bertalanffy, Logistic, and Gompertz. Results showed that the degree of goodness fit of the four models classifies high in the category (R 2 > 0.84). Brody model was most appropriate in describing the Brahman female cattle growth curve. Logistic and Gompertz models were most appropriate in predicting Brahman female cattle mature weight. Keywords: Breeding, Brody, Growth curve, Mature weight, Nonlinear